Las estrellas de Orión - Andreea Ciobanu (Latin American Literary Review, 2023)
A pregnant woman enters a grocery store in the middle of the pandemic. She bears the weight of work, familial drama, and the future. Her experiences highlight the obstacles employed women face in the United States and the lack of social concern and support for expecting mothers.